Validity and reliability of the SF-36 in Chilean older adults: the ALEXANDROS study. - Lera, Lydia; Fuentes-García, Alejandra; Sánchez, Hugo; Albala, Cecilia (European Journal of Ageing, 2013)
To validate short-form-36 health survey (SF-36) with specific scoring algorithm obtained in a large sample of Chilean older people and to associate quality of life in this sample with social and health related factors. A cross-sectional study on 2,143 community-living subjects aged 60-92 years (33 % men and 67 % women) conducted in Santiago, Chile. Scores in 8 scales of SF-36-physical function (PF), role physical (RP), bodily pain (BP), general health (GH), vitality (VT), social functioning (SF), role emotional (RE) and mental health (MH)-, were calculated. Factor analysis was used to extract two principal factors and logistic regression model was applied to estimate its association with socio-demographic and health variables. The internal consistency of scales was high (Cronbach's alpha 0.86-0.87). Factor analysis retained two factors: mental (MCS) and physical (PCS) components accounting for 65.3 % of total variance (55.3 and 10.0 % respectively). High correlations (0.61-0.94) between MCS and MH, V, RE and SF were obtained. PCS correlated highest (0.72-0.86) with RP, PF and BP. Self-perceived symptoms of depression (GDS-15 ≥5) was the main variable explaining low scores in both MCS and PCS (adjusted OR = 26.9; 95 % CI: 15.3-47.2; OR = 3.4; 95 % CI: 2.1-5.5, respectively). We have demonstrated the reliability and validity of SF-36 questionnaire to evaluate health related quality of life, reporting Chilean-Specific factor score coefficients for MCS and PCS based in national Chilean means and standard deviations for older people. After adjusting by age and gender, the main predictors of low health related QoL in Chilean older people were self-perceived symptoms of depression, the presence of two or more chronic diseases and illiteracy. Important gender inequalities were observed in all of these results, being consistently less favorable in women than in men.